The combination of checkpoint immunotherapy and targeted therapy in cancer - Karachaliou, Niki; Gonzalez Cao, Maria; Sosa, Aaron; Berenguer, Jordi; Paulina Bracht, Jillian Wilhelmina; Ito, Masaoki; Rosell, Rafael (Annals of Translational Medicine; Vol 5, No 19 (October 28, 2017): Annals of Translational Medicine (Focus on “II Meeting on Traslational Research on Melanoma by the Spanish Melanoma Group (GEM)”), 2017)
The therapeutic possibilities for patients with metastatic melanoma have changed due to the development of targeted therapies that inhibit oncogenic signaling pathways as well as immune modulating therapies that unleash the patient antitumor immunity. These therapeutic changes have impressively increased the median overall survival of the patients. Considering the dramatic but transient responses that occur with targeted therapies for a subgroup of patients and the durable responses that can be achieved with immunotherapy in a subset of patients, a lot of effort is ongoing for the clinical development of combinations of these two therapeutic approaches. Herein we discuss the existing preclinical and clinical data for the combination of targeted therapies and immunotherapy focusing mainly on melanoma and non-small cell lung cancer (NSCLC).